Cultivating participatory processes in self‐harm app development: A case‐study and working methodology - Camilla M. Babbage; Joanna Lockwood; Lily Roberts; Josimar Mendes; Chris Greenhalgh; Lucy‐Paige Willingham; Emmanuel Wokomah; Rebecca Woodcock; Petr Slovak; Ellen Townsend; the Digital Youth research team (JCPP Advances)
Abstract Background Self‐harm and suicide related behaviours are increasing in young people, and clinical support is not adequately meeting needs. Improved approaches to assessment and the clinical management of self‐harm will result from codesign processes and include greater shared decision‐making between young people and practitioners. The CaTS‐App (an adapted digital version of the existing Card‐Sort Task for Self‐harm research tool) aims to facilitate a collaborative understanding of adolescent self‐harm and support decision‐making within clinical settings. The codevelopment of a digital, clinical tool which meets the needs of multiple stakeholders requires careful consideration. Methods We present a case‐study describing the participatory aspects of the development of the CaTS‐App, which included comprehensive patient involvement, research activities and coproduction with diverse young people aged 17–24 with lived experience of self‐harm. We share our processes and activities to deliver safe, engaging, sustainable, ethical and responsible participatory practice and co‐created knowledge, in the codevelopment of the CaTS‐App. Results Activities spanned a 48‐month period in both face‐to‐face and online settings. Example processes and activities are provided in narrative, tabular and diagrammatic form, alongside discussion of the rationale for choices made. A summary methodology is also shared to stimulate continued discussion and development of participatory approaches in digital mental health. Conclusions The paper contributes important insight and practical detail for the delivery of genuine participatory processes in digital mental health development when working with a population who may be considered vulnerable.